Addition of Hydrogen Peroxide to Groundwater with Natural Iron Induces Water Disinfection by Photo‐Fenton at Circumneutral pH and other Photochemical Events. (26th June 2017) - Gutiérrez‐Zapata, Héctor Mario; Alvear‐Daza, John Jairo; Rengifo‐Herrera, Julián Andrés; Sanabria, Janeth
Abstract: Samples of natural groundwater (with low turbidity, neutral pH and 0.3 mg L −1 iron concentration) inoculated with Escherichia coli K‐12 were exposed to simulated solar light both in the presence and in the absence 10 mg L −1 of H2 O2. Results demonstrated that the viability of E. coli (by DVC–FISH) was grounded to zero after 360 min of irradiation. This abatement could be caused by the oxidative stress induced by · OH radicals or another photo‐induced reactive oxygen species. Two 2 3 factorial experimental designs enabled the evaluation of the effects of chemical factors on the inactivation of E. coli . The first experimental design considered the pH, iron and H2 O2, while the second evaluated the ions fluoride, carbonate and phosphate found in groundwater. pH was found to play a key role in the inactivation of E. coli . The best reduction in viability was obtained at the lower pH (6.75), while a nonsignificant effect was observed when iron or H2 O2 concentrations were raised. At higher concentrations, anions, such as carbonate and phosphate, negatively affected the E. coli abatement. However, a higher concentration of fluoride accelerated it. In all experiments, the pH was observed to rise to values higher than 8.0 units after 360 min of treatment. Abstract : It is possible to inactivate E. coli cells in natural groundwater samples that already contain iron by the simple addition of 10 mg L −1 of H2 O2 and subsequent irradiation with simulated solar light. Different photochemical processes leading to the production of reactive oxidative species (ROS) could be involved as follows: circumneutral photo‐Fenton by dissolved or colloidal iron, photocatalysis by metallic oxides or iron (hydr)oxides, and photochemical by dissolved organic matter excitation, H2 O2 photolysis and nitrate/nitrites light‐absorption. Fluoride used at 1.2 mg L −1 exhibited a positive effect. Furthermore, CO3 2− could react with · OH radicals producing CO 3 − · which could be toxic to microorganisms.